Cyfrinach Betsan Morgan - Hywyn, Gwenno,Jones, Jac (Y Lolfa, 2022)
A mystery story with a twist. Betsan Morgan isn't looking forward to spending a week with her classmates at Plas yr Hydd. Her best friend is ill at home, and she has to go on her own, with strangers. But once she arrives, Betsan finds that she is able to travel to the past to live in the time of her great-great-great-grandmother. Intro – Pennod 1 – Pennod 2 – Pennod 3 – Pennod 4 – Pennod 5 – Pennod 6 – Pennod 7 – Pennod 8 – Pennod 9.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books